Effects of Interventions to Raise Voluntary Enrollment in a Social Health Insurance Scheme A Cluster Randomized Trial - Capuno, Joseph J. (The World Bank, 2014)
A cluster randomized controlled trial was undertaken, testing two sets of interventions to encourage enrollment in the Philippines' Individual Payer Program. Of 243 municipalities, 179 were randomly assigned as intervention sites and 64 as controls. In early 2011, 2,950 families were interviewed; unenrolled Individual Payer Program-eligible families in intervention sites were given an information kit and a 50 percent premium subsidy until the end of 2011. In February 2012, the "non-compliers" had their voucher extended, were re-sent the enrollment kit, and received Short Message Service (SMS) reminders. Half were told that in the upcoming end-line interview the enumerator could help complete the enrollment form, deliver it to the insurer, and have identification cards mailed. The control and intervention sites were balanced at baseline. In the control sites, 9.9 percent (32/323) of eligible individuals had enrolled by January 2012, compared with 14.9 percent (119/801) in intervention sites. In the sub-experiment, enrollment was 3.4 percent (10/290) among eligible non-compliers and who did not receive assistance but 39.7 percent (124/312) among those who did. A premium subsidy combined with information can increase voluntary enrollment in a social health insurance program, but less than an intervention that reduces the enrollment burden; even that leaves enrollment below 50 percent